Are Patients Willing to Use a Smart Scale?. (29th May 2020) - Mafong, Kaley; Kim, Sally; Fujioka, Ken
Abstract: Objectives: Smart Scales are electronic scales that can store and track data (weights) with the ability to send data to an internet based portal. This data could go to the Health Care Provider (HCP) to help with weight management. It is known that patients that weigh frequently (more than once a week vs. weekly or monthly) will lose more weight than patients who do not.The objective is to determine if patients are willing to weigh daily and use a smart scale that would transmit their weight to their HCP. Methods: A questionnaire was given to 100 consecutive primary care health insured patients willing to answer questions about usual practices of weighing (daily, weekly, monthly), whether the patient owns a scale, would they be willing to weigh daily, would they use a smart scale, would they be willing to share this data with their HCP, and would they purchase such a scale. Results: Demographics: the average BMI was 28.4, 84% female, 18% of patients age 18 to 39.9 years of age, 35% age 40–64.9, 47% age 65 or higher. 48% were Caucasian, 31% Hispanic, 21% Asian, 4% African American (several patients identified with more than one race). 85% of patients owned a scale. 70% of patients weigh themselves at home. 25% weight less than once a month. 69% weight monthly or more, 41% weigh weekly or more, and 20% weigh daily (or most days of the week). Questionnaire answers: 72% of the patients would be willing to use a smart scale. 66% of patients would be willing to weigh daily and 65% of patients are willing to have this data communicated to their HCP. 54% of patients would not be willing to buy a smart scale and of those willing to buy a smart scale the price would need to be between $45 and $30 US dollars for the majority of the patients. 2% felt they could not afford a smart scale. Conclusions: Health care is changing towards more telemedicine for appropriate disease states. Obesity or weight management may be ideal for this type of health care. Frequent self-weighing with a smart scale would be a good fit in this setting. This study shows that the majority of patients do not weigh frequently, but would be willing to weigh daily, and have this data transmitted to their HCP. Unfortunately just over half (54%) of the patients would not be willing to buy a smart scale and 2% cannot afford a smart scale. Funding Sources: None.